PENGEMBANGAN JANGKAUAN PEMASARAN UMKM DENGAN MENINGKATKAN PENGETAHUAN DIGITAL MARKETING PADA MASYARAKAT DESA KARYAMEKAR - Susetyaningsih, Adi; Dermawan, Dena Kamal; Hidayat, Abdul Rojak; Novianty, Nindita; Saharah, Helmi; Hidayat, Fahreza Pratama; Najata, Sulton Aulia; Dafa, Daril Muhamad; Mardiah, Ilma Hayatul; Romadhona, Naufan; Nugroho, Satryo Bimo; Tofan, Inggit Hardiyanti; Herlina, Julia; Totti, Devor Sebastian; Barkah, Fauzi; Nurohman, Sendi Rijali; Welianda, Muhammad; Syahrani, Firah Aulia; Rahmattuloh, Gilang Ramadhan; Dwiputra, Erdi Rizky; Muharram, Moch Raihan; Al-Ghani, Davin (Jurnal PkM MIFTEK, 2025)
Karyamekar Village is located in Cilawu District, Garut Regency. Most of its residents still rely on the agricultural and trade sectors as a livelihood. Although it has a lot of potential to be developed, the low level of education and limited knowledge of the community about digital marketing are one of the main obstacles for Micro, Small and Medium Enterprises (MSMEs) in this village to expand their market share. Through an integrated approach in various KKN ITG programs, digital marketing-themed training was carried out which aimed to increase the reach of the MSME market in Karyamekar Village. The results of the training showed a significant increase in community understanding of digital marketing from 32.5% before training to 62.5% after training. This program not only improves the marketing skills of MSME actors, but also helps them utilize digital platforms such as e-commerce and social media to increase the competitiveness of their products. Digital marketing training for MSME actors is effective in overcoming the limitations of traditional marketing and can contribute to improving the local economic welfare of Karyamekar Village.